Translation and validation of the Treatment Motivation Questionnaire TMQ to Malay version - Engku Kamarudin, Engku Mardiah; Zainuddin, Zaida Nor; Mohamad Yusop, Yusni; Mohd Noor, Amelia; Mahmud, Mohd Izwan (Human Resource Management Academic Research Society, 2021)
Introduction: Motivation plays a significant role in treating any illness, especially for patients with addiction problems. Moreover, motivation is a factor that influences patients to look for treatment possibilities, follow instructions of the treatment, and mainly make prosperous longterm changes. Objective: The purposes of this study are to translate and validate the Malay version of the Treatment Motivation Questionnaire (TMQ) among opioid use disorders in Methadone treatment. This questionnaire is to study patient's motivation for entering treatment. Method: Translation, back-translation, pilot testing, and validation of the final TMQ were all part of the four-phase technique for translating and validating generic questionnaires. The intercorrelation item and the Cronbach's alpha coefficient were used to assess the final TMQ's overall internal consistency. Results: The Malay TMQ had excellent Cronbach’s alpha values of 0.942. In addition, it had a good factor loading values for most items except one item under ‘confidence in treatment’ (r=0.0082) and eliminating that item from scoring increased the alpha coefficient of the scale of TMQ. Correlations among scales were between .616 and .96. Conclusions: This study demonstrates that the Malay version of the TMQ is a valid and reliable tool used to measure treatment motivation in Malay-speaking populations.